Antioxidant Nutrient Density of Local Foods: Content of Vitamin C in Selected Fruits and Vegetables of Bangladesh - Mohiduzzaman, Md; Karim, Kazi Muhammad Rezaul; Rahim, Abu Torab MA; Shaheen, Nazma (Bangladesh Journal of Nutrition, 2019)
The study was carried out on 3 fruits and 6 vegetables. The samples were collected from the different locations covering the 30 agro-ecological zones of Bangladesh so that the study qualifies as a representative composite nutrient analysis. The proximate nutrients content was analyzed by AOAC method, while the antioxidant nutrient such as vitamin C (L-ascorbic acid) was measured by HPLC method. Ripe Mango (Langravarity) and green chili are rich source of antioxidant nutrient Vitamin C (L-ascorbic acid, about 103mg and 102mg/100g raw edible portion for mango and green chili, respectively); potato (Diamond variety), tomato and bean were found to contain medium amount of Vitamin C among the selected fruits and vegetables. Bangladesh J. Nutr. Vol. 32, December 2019, P: 1-4